The Effect of Smear Layer on Antimicrobial Efficacy of Three Root Canal Irrigants - Zargar, Nazanin; Dianat, Omid; Asnaashari, Mohammad; Ganjali, Mojtaba; Zadsirjan, Saeede (Iranian Endodontic Journal, 2015)
Introduction: One of the main goals of endodontic treatment is to decrease the harboring bacteria within the root canal system and dentinal tubules. This experimental study attempted to investigate the antibacterial efficacy of three root canal irrigants in the presence and absence of smear layer (SL). Methods and Materials: A total of 210 sound extracted human single-rooted teeth were prepared. After creating the SL and its removal in half of the samples, they were infected with Candida albicans (C. albicans) and Actinomyces israelii (A. israelii). A total of 180 specimen were used to assess the antimicrobial efficacy of the three irrigants in presence and absence of SL, 24 specimen were placed in the positive and negative controls, 2 samples were utilized for scanning electron microscopy (SEM) analysis and 2 were used for Gram staining. Then, they were exposed to irrigants including 2.61% sodium hypochlorite (NaOCl), 0.2% chlorhexidine gluconate (CHX) and 1% povidone-iodine (PI) for 5, 30 and 60 min. Presence/absence of test microorganisms was determined by incubation of specimens in test tubes containing brain-heart infusion (BHI) broth and then measuring the colony forming units (CFU) on BHI agar. A cumulative logistic model was used to analyze the ordinal response. Results: The 2.61% solution of NaOCl was significantly more effective than 0.2% CHX and the latter was more efficient than 1% PI for decreasing fungal and microbial infection of dentinal tubules in the presence and absence of SL. Conclusion: The presence of smear layer decreased the efficacy of antimicrobial irrigants. The minimum time required for elimination of fungal/microbial infection was 30 min. Keywords: Actinomyces israelii; Candida albicans; Chlorhexidine; Povidone-Iodine; Smear Layer; Sodium Hypochlorite